Clinical and neurophysiological biomarkers of disease progression in amyotrophic lateral sclerosis. Issue 1 (25th October 2022) - Hannaford, Andrew; Byth, Karen; Pavey, Nathan; Henderson, Robert D.; Mathers, Susan; Needham, Merrilee; Schultz, David; Menon, Parvathi; Kiernan, Matthew C.; Vucic, Steve
Abstract: Introduction/Aims: Rate of disease progression (ΔFS), measured as change in the revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS‐R) and body mass index (BMI), are predictors of survival in amyotrophic lateral sclerosis (ALS). Our aim in this study was to assess the utility of these clinical biomarkers along with neurophysiological measures, such as the split hand index (SI), in monitoring disease progression. Methods: Clinical trial data were collected from 107 patients recruited into the Tecfidera in ALS trial. The prognostic utility of clinical and neurophysiological measures, including ΔFS, BMI, SI, and neurophysiological index (NPI), were assessed cross‐sectionally and longitudinally (40 weeks). The outcome measures of disease severity and progression included: (i) ALSFRS‐R score; (ii) Medical Research Council (MRC) score; and (iii) forced vital capacity and sniff nasal inspiratory pressure. Results: Fast‐progressor ALS patients (ΔFS ≥1.1) exhibited significantly lower ALSFRS‐R and total MRC scores at baseline. A baseline ΔFS score ≥1.1 was associated with a greater reduction in ALSFRS‐R ( P = .002) and MRC ( P = .002) scores over 40 weeks. Baseline BMI <25 was also associated with faster reduction of ALSFRS‐R and MRC scores. SI and NPI were associated with disease severity at baseline, but not with subsequent rate of disease progression. Discussion: Implementation of the assessed clinical and neurophysiological biomarkers may assist in patient management and stratification into clinical trials.